The Use of Antigenic SARS-CoV-2 Point-of-Care Test: The Italian Pediatric Real-Life Experience. (January 2022) - Ferrari, Federica; Civitelli, Fortunata; Ardenti Morini, Francesca; Buonaiuto, Federico Angelo Carmelo; Frega, Gianluca; Fabbri, Francesca; Ioppi, Mauro; Maione, Alberto; Minniti De Simeonibus, Elena; Soscia, Francesca; Torre, Piera; Toselli, Francesca; et al.
In Italy, during the second epidemic wave of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapid antigenic (Ag) test at point-of-care (POCT) station were employed to quickly evaluate large numbers of swabs. We collected data of all children who underwent the Ag test in our hospital. All positive patients were recalled to perform reverse transcription polymerase chain reaction. A total of 2133 tests were collected over 1 month. Clinical data of 1941 children (median age = 3.7 years) were analyzed: 1343 (69.2%) patients complained of symptoms, 594 (30.6%) had a history of close contact with SARS-CoV-2-positive individuals. Among symptoms reported, acute rhinitis was the most frequent (67.9%), followed by cough (42.6%) and fever (31.5%). Among all tests, 95.8% resulted negative, 4.2% positive: 37/89 were confirmed. In confirmed cases, fever (56.2% vs 32.2%; P = .041) and gastrointestinal symptoms (18.8% vs 6.25%; P = .041) were significantly more frequent compared with negative children. The use of POCT for Ag test seems appropriate for SARS-CoV-2 screening in the pediatric population. In children, fever and gastrointestinal symptoms may constitute red flags of SARS-CoV-2.